2023
DOI: 10.1158/0008-5472.can-22-2496
|View full text |Cite
|
Sign up to set email alerts
|

ASPM Activates Hedgehog and Wnt Signaling to Promote Small Cell Lung Cancer Stemness and Progression

Abstract: Small cell lung cancer (SCLC) is among the most aggressive and lethal human malignancies. Most patients with SCLC who initially respond to chemotherapy develop disease relapse. Therefore, there is a pressing need to identify novel driver mechanisms of SCLC progression to unlock treatment strategies to improve patient prognosis. SCLC cells comprise subsets of cells possessing progenitor or stem cell properties, while the underlying regulatory pathways remain elusive. Here, we identified the isoform 1 of the neu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…ASPM positively regulates the protein stability of its binding partners, such as cyclin E, DVL, GLI1, and BRCA1, in neuro‐progenitor cells and cancer cells [18,19,21,29,34,35]. Since the expression of NICD is under strict regulation by specific E3‐ubiquitin ligases [36,37], we posited that ASPM‐i1 might regulate the protein stability of NICD1 in HCC cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…ASPM positively regulates the protein stability of its binding partners, such as cyclin E, DVL, GLI1, and BRCA1, in neuro‐progenitor cells and cancer cells [18,19,21,29,34,35]. Since the expression of NICD is under strict regulation by specific E3‐ubiquitin ligases [36,37], we posited that ASPM‐i1 might regulate the protein stability of NICD1 in HCC cells.…”
Section: Resultsmentioning
confidence: 99%
“…The development-associated Notch signaling pathway is activated in a considerable subset of human HCC and contributes to tumor development and progression [10][11][12]. The reported roles of ASPM in neurogenesis and development-associated pathways, such as the Wnt and Hedgehog signaling pathways [29], prompted speculation about its role in the Notch pathway in HCC cells. Consistently, gene set enrichment analyses (GSEA) of the TCGA-LIHC data set revealed that the Notch pathway gene sets are significantly enriched in patients with HCC with high ASPM expression (Fig.…”
Section: Aspm-i1 Contributes To the Notch Signaling Pathway Activity ...mentioning
confidence: 99%
“…26 ASPM has also been shown to promote cancer progression. 27,28 TOP2A and CDNK3 have been screened to be involved in colorectal cancer progression. 29 Currently, TOP2 has been widely used in targeted therapy of cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al identify 14 key genes related to the pathogenesis of colon cancer, including CEP55, TOP2A, RRM2, NCAPG2, providing new directions for elucidating the molecular mechanisms of colon cancer 26 . ASPM has also been shown to promote cancer progression 27,28 . TOP2A and CDNK3 have been screened to be involved in colorectal cancer progression 29 …”
Section: Discussionmentioning
confidence: 99%
“…In summary, aberrant Wnt/β-catenin activation maintains LC stem cell-like characteristics and promotes LC progression. The Wnt/β-catenin signaling pathway has been implicated in the regulation of CSCs, although the underlying regulatory pathways of CSCs remain elusive ( Cheng et al, 2023 ).…”
Section: Wnt/β-catenin In Lcmentioning
confidence: 99%